2019
DOI: 10.1186/s12884-019-2336-1
|View full text |Cite
|
Sign up to set email alerts
|

‘If nurses were in our shoes would they breastfeed their own babies?’ A qualitative inquiry on challenges faced by breastfeeding mothers on the PMTCT programme in a rural community in Zimbabwe

Abstract: Background The Prevention of Mother to Child Transmission (PMTCT) of HIV programme in Zimbabwe has had remarkable success despite the country’s economic challenges. The aim of this study was to explore the challenges faced by breastfeeding mothers on the PMTCT programme. Method Narratives from 15 women (age range 19–35 years) were collected at two rural health facilities in Zimbabwe through in-depth interviews over a period of 6 months. Thematic analysis was used to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Of the 56 studies included in this review, 8 (14.3%) reported infrastructural barriers [ 30 – 37 ] while only one study (1.8%) reported facilitators [ 38 ]. Most frequently described barriers to postnatal breastfeeding support were overcrowding and lack of space [ 30 – 32 , 34 36 ]. For example, a study from Ghana reported that increases in caesarean deliveries was associated with overcrowding and insufficient equipment, which led to moving new mothers out of delivery quickly to make room for the next woman in labour [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 56 studies included in this review, 8 (14.3%) reported infrastructural barriers [ 30 – 37 ] while only one study (1.8%) reported facilitators [ 38 ]. Most frequently described barriers to postnatal breastfeeding support were overcrowding and lack of space [ 30 – 32 , 34 36 ]. For example, a study from Ghana reported that increases in caesarean deliveries was associated with overcrowding and insufficient equipment, which led to moving new mothers out of delivery quickly to make room for the next woman in labour [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lack of privacy, a quiet place to breastfeed, availability of chairs for mothers to sit and breastfeed in and unreliable access to water and electrical power were also infrastructural challenges to breastfeeding at health facilities [ 33 , 35 – 37 ]. For example, a study from Zimbabwe highlighted how health workers asked mothers questions related to their HIV status while other patients were listening, which compromised confidentiality and decreased the likelihood of initiating breastfeeding [ 36 ]. In the one study that described infrastructural facilitators, the researchers in Tanzania reported that wall clocks and cell phone alarms supported regular timing feedings of low birthweight infants [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations